Suka Jaya Travel & Tours (SJTT) / Abdul Mutalib Azman - Azman, Abdul Mutalib (Universiti Teknologi MARA, Perlis, 2024)
This research paper provides a profile of the internship place, Suka Jaya Travel & Tours (SJTT). The well-established SJTT travel firm offers unique holiday experiences to individuals, families, and groups. SJTT is a trusted tourist authority with over two decades of experience in inbound and outbound travel, ticketing, and Umrah & Ziarah programs. This research paper also examines how human capital efficiency affects Malaysian plantation financial performance. The study examines financial metrics and human capital efficiency. The report also suggests ways to improve industrial human capital efficiency. The research uses a strong methodology and extensive data analysis. The research shows that human capital efficiency is vital to Malaysian plantation companies' financial performance. Human capital efficiency improves financial indicators like return on assets and asset turnover ratio. The study also shows that firm size, leverage, and age affect human capital efficiency and financial success. In conclusion, this study illuminates how human capital efficiency affects Malaysian plantation financial performance. It stresses the importance of human capital development and proposes ways to improve efficiency. It also details SJTT, the internship site, and its dedicated management team directed by Haji Abdul Shukor Bin Mohammed Zainuri.